DAMPAK ADOPSI CLIMATE-SMART AGRICULTURE TERHADAP KINERJA USAHATANI: TINJAUAN LITERATUR SISTEMATIS 2015–2025 - Nimah, Lulua Ulyn; Sasongko, Lutfi Aris (Universitas Wahid Hasyim, 2025)
This systematic review synthesizes empirical evidence from 2015-2025 on the impacts of Climate-Smart Agriculture (CSA) adoption on farm performance. While CSA is promoted to raise productivity, strengthen resilience, and reduce emissions at the farm level, empirical findings remain fragmented and performance indicators are not yet standardized. This review systematically assesses effects during 2015-2025 on a core set of farm-level indicators yield (t ha⁻¹), cost (USD PPP ha⁻¹), margin/return on investment (ROI), income volatility, resilience, and environmental outcomes distinguishing single practices from bundled packages in the context of Indonesia and the broader ASEAN region. We searched Scopus, Web of Science, ScienceDirect, SpringerLink, and Google Scholar (2015-2025), normalized data to common units (t ha⁻¹, USD PPP ha⁻¹, CO₂e ha⁻¹), and conducted an analytical-comparative synthesis. Water-efficiency practices (e.g., alternate wetting and drying/AWD) generally maintained or increased yields, lowered water/energy costs, and curtailed CH₄ emissions. Multi-season field studies reported 21-73% reductions in CH₄ and 26-29% declines in global warming potential (GWP), contingent on adequate nitrogen management. Conservation agriculture improved soil health and medium-term profitability. Moreover, bundled practice packages (e.g., water-nitrogen-advisory) more consistently delivered multidimensional benefits than single practices. Heterogeneity is driven primarily by agroecology, asset and service access, and commodity (predominantly rice), warranting caution when generalizing to non-rice systems. Overall, evidence from 2015-2025 supports scaling CSA packages in tandem with lightweight measurement, reporting, and verification (MRV) based on standardized farmer-level indicators to ensure that technical gains translate into measurable economic and environmental benefits.